Internet- and mobile-based aftercare and relapse prevention interventions for anxiety and depressive disorders: a systematic review - Petre, Ligiana Mihaela; Piepiora, Paweł Adam; Gemescu, Maria; Gheorghe, Delia Alexandra (Frontiers in Psychology, 2024)
BackgroundDigital interventions present potential solutions for aftercare and relapse prevention in anxiety and depressive disorders. This systematic review synthesizes evidence on the efficacy of internet- and mobile-based interventions for post-acute care in these conditions.MethodsA systematic search was conducted in electronic databases (MEDLINE, CENTRAL, Scopus, Web of Science, PsycINFO, PsycARTICLES, PsycEXTRA, ProQuest Dissertations and Theses Open, Open Access Theses and Dissertations, and Open Grey) for randomized controlled trials evaluating digital aftercare or relapse prevention interventions for adults with anxiety or depressive disorders. Primary outcomes included symptom severity, relapse rates, recurrence rates, and rehospitalization. Secondary outcomes included general quality of life and adherence to primary treatment. Risk of bias was assessed using the Cochrane tool.ResultsNineteen studies (3,206 participants) met the inclusion criteria. Interventions included cognitive-behavioral therapy, mindfulness-based approaches, and supportive text messaging. Most studies focused on depression, with limited evidence for anxiety disorders. Notably, fourteen studies that reported on depressive symptoms demonstrated significant improvements following digital interventions, with effect sizes ranging from small (Cohen’s d = 0.20) to large (Cohen’s d = 0.80). Five studies investigated relapse or recurrence rates, yielding mixed results. Adherence rates varied significantly across studies, ranging from 50 to 92.3%, highlighting the variability in participant engagement. Methodological quality was also variable, with allocation concealment and blinding being common limitations.ConclusionInternet- and mobile-based interventions show promise for aftercare and relapse prevention in depression, with limited evidence for anxiety disorders. Future research should focus on optimizing engagement, personalizing interventions, standardizing outcome measures, and conducting larger trials with longer follow-up periods. These findings have important implications for integrating digital tools into existing care pathways to improve long-term outcomes for individuals with anxiety and depressive disorders.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020151336, CRD42020151336.